Practitioner Profile: An Interview with Reeta Wolfsohn, CMSW - Reeta Wolfsohn (Journal of Financial Therapy, 2014)
Reeta Wolfsohn, CMSW, began practicing financial therapy in 1997. At the time, she didn’t call what she did by that name, but her work specifically addressed the financial issues and problems of her clients. Early on in her work, Reeta recognized clients wanted to take control of their money and their lives, but struggled not only with the shame, guilt, worry, and stress of debt, but also with the poor sense of self, and low self-confidence and self-esteem which inevitably accompanied it. Realizing clients needed more help than regularly scheduled therapy sessions, she began developing financial educational materials and psychosocial financial activities for her clients to work on between sessions. Financial Social Work grew out of those early efforts.
Keywords: financial therapy; financial social work; social work; Wolfsohn